2020
DOI: 10.3390/en13226128
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Emission Reduction—Carbon Tax, Carbon Trading, and Carbon Offset

Abstract: The Paris Agreement was signed by 195 nations in December 2015 to strengthen the global response to the threat of climate change following the 1992 United Nations Framework Convention on Climate Change (UNFCC) and the 1997 Kyoto Protocol [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Furthermore, the same study was also conducted for the assessment of carbon emissions in industrial companies in China, it was found that these policies only contribute to a certain extent and will decrease over time [31]. While contrasting results were also found for China, that carbon trading was effective in reducing carbon emissions [32]. A different study was conducted on reducing carbon emissions through emission transfers in China, it was found that imports of carbon emissions were greater [33].…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, the same study was also conducted for the assessment of carbon emissions in industrial companies in China, it was found that these policies only contribute to a certain extent and will decrease over time [31]. While contrasting results were also found for China, that carbon trading was effective in reducing carbon emissions [32]. A different study was conducted on reducing carbon emissions through emission transfers in China, it was found that imports of carbon emissions were greater [33].…”
Section: Introductionmentioning
confidence: 98%
“…The study provides details about four normalized green building metrics (indices) that can be used as generic targets or benchmarking levels to compare with, when assessing the level of sustainability of other buildings in Oman, either without taking sustainability measures into account (the base case) or with adopting them (the design case). The green building design presented here is classified as a ZCRB (Zero Carbon Ready Building) or a renewable energy ready building [26,27], which means that the building design does not only show satisfactory levels of savings in energy, water, and materials, but also has the potential to be a net-zero source of greenhouse gases without major retrofitting in the future, either through purchasing renewable energy from an offsite source, such as using a power purchase agreement (PPA [28,29]), or through purchasing enough carbon offsets [30,31] to counteract greenhouse gases released from operating the building. In the ZCRB design presented here, it was intended to adopt enough changes in the base building to meet the certification requirement, while minimizing the excess in compliance beyond the minimum requirements.…”
Section: Goal and Contribution Of The Studymentioning
confidence: 99%
“…To comply with the Paris Agreement [ 2 ], which aims to keep the rise in mean global temperature below 2 °C, countries such as Malaysia intend to reduce carbon emissions by 45% by 2030 [ 2 ]. Globally, many methods, such as introducing carbon taxation/trading schemes [ 3 , 4 ], renewable energy [ [5] , [6] , [7] ], improving efficiency [ 8 ] and carbon-capturing technology [ [9] , [10] , [11] ], have been introduced to reduce CO 2 emissions. However, fossil fuel usage is inevitable for the industry, especially in Malaysia, due to high energy generation that leads to high amounts of electricity generated at once [ 12 ].…”
Section: Introductionmentioning
confidence: 99%